Analysis of the Addition of Binding Wire and Ethylene Vinyl Acetate on the Stability and Flow Performance of Asphalt Treated Permeable Superpave for Coastal Road Pavement - Ferdiano Yogi Pradana; Rachmat Mudiyono (JACEE (Journal of Advanced Civil and Environmental Engineering), 2026)
The Pantura (Northern Coast) national road in Indonesia, frequently experiences problems with waterlogging, mostly caused by extreme weather conditions such as continuous rain, resulting in flooding and rising sea levels that inundate the road construction. To address these issues, an unconventional asphalt pavement design is needed. This study aims to create a Superpave (Superior Performing Asphalt Pavements) graded asphalt composition with EVA (Ethylene Vinyl Acetate) and Binding Wire additives that are expected to meet Marshall and Permeability criteria. The method used in this study is an experimental study. Test specimens were prepared and subjected to Marshall and Permeability tests. The specimens were prepared using EVA (Ethylene Vinyl Acetate) additives of 0%, 1%, 3%, and 5% and Binding Wire at 0%, 2%, 4%, 6%, and 8%. In the research results, along with the increasing percentage of EVA and Binding Wire, the highest stability value was obtained in the E0B8 Cement material variation of 2578.99 Kg. The highest Flow value was in E5B5 Cement of 3.90 mm. The highest Marshall Quotient value was in E0B8 Lime of 701.55%. The highest Void in Mineral Aggregate (VMA) and Void Filled with Asphalt (VFA) values were obtained in the E0B0 Lime material variation of 20.51% and 84.70%, respectively. The highest Void in The Mix (VIM) value was obtained in E5B8 Cement of 4.63%. While the highest Dry Density Permeability was in E5B8 of 0.92 gr/cm2 Cement and the highest Permeability Coefficient was in E0B4 of 1.64528×10-5 gr/cm Limestone.